THE RELATIONSHIP OF SOCIO ECONOMIC STATUS WITH DIET COMPLIANCE IN TYPE 2 DIABETES PATIENTS IN THE WORKING AREA OF THE SOUTH SUMEDANG HEALTH CENTER - Zulfah Ummu Masyhuroh; Dewi Dolifah; Delli Yuliana Rahmat (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Blood sugar levels must be well controlled to reduce the risk of complications. Due to people's unhealthy lifestyles, the number of Diabetes Mellitus sufferers increases every year. Non-communicable diseases are defined as diseases that cannot be transmitted from one person to another. The general aim of the research is to determine the relationship between socio-economic status factors and the compliance of type 2 diabetes mellitus sufferers in implementing a diet. The method used in this research is quantitative correlation. Quantitative research is an approach to testing certain theories by examining the relationships between variables. There is an important relationship between economic status and adherence to dietary patterns, with a significance value of 0.029. Of the 110 respondents surveyed, the data showed that there were differences in the distribution of dietary compliance between groups with low and high socio-economic status. Identifying elements that influence the level of compliance in following a diet in individuals with Diabetes Mellitus. It is hoped that Community Health Centers and hospitals can increase patient knowledge about diabetes mellitus and ensure their awareness.